Past-year opioid misuse and suicide attempt are positively associated in high suicide risk veterans who endorse past- year substance use. (December 2019) - Chesin, Megan; Interian, Alejandro; Kline, Anna; St. Hill, Lauren; King, Arlene; Miller, Rachael; Latorre, Miriam; Stanley, Barbara
Abstract: The main purpose of this study was to test the relationship between past-year suicide attempt (SA) and past-year opioid misuse among Veterans at high risk of suicide who reported using at least one illicit substance or alcohol in the past year. Baseline data from 130 high suicide-risk Veterans ( n  = 39 past-year opioid misusers; n  = 91 past-year users of other substances) who enrolled in a randomized controlled trial testing adjunctive Mindfulness-Based Cognitive Therapy to Prevent Suicidal Behavior were used. Information was collected on a semi-structured interview that included the Columbia-Suicide Severity Rating Scale to collect suicide attempt history. Past-year opioid misusers, compared to those who used at least one other illicit substance or alcohol in the past year, were more likely to have made a past-year SA. Past-year opioid misuse remained associated with past-year SA in multivariate analysis that included other known risk factors for SA. Our findings show a robust link between near-term SA and opioid misuse in Veterans. Highlights: Past-year opioid misuse is associated with past-year suicide attempt in high suicide-risk Veterans. The relationship between past-year opioid misuse and past-year suicide attempt remains when psychosocial factors associated with suicide attempt and opioid misuse are included as covariates. Suicide attempt rates do not differ among those by type of opioid used.